FAKTOR-FAKTOR YANG BERPERAN TERHADAP PENINGKATAN SIKAP KESELAMATAN DAN KESEHATAN KERJA (K3) PARA PELAKU JASA KONSTRUKSI DI SEMARANG - Endroyo, Bambang (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract:ÃÂ  ImplementationÃÂ  of Occupational HealthÃÂ  and SafetyÃÂ  (K3),ÃÂ  especiallyÃÂ  inÃÂ  theÃÂ  construction sector was still bad. K3ÃÂ  inÃÂ  IndonesiaÃÂ  is haveÃÂ  theÃÂ  lowestÃÂ  rankÃÂ  in Asean. Various efforts have been made by governmentÃÂ  to reduce occupational accidentsÃÂ  to a minimum as possible. Accidents often occur were mostly caused by humanÃÂ  factors,ÃÂ ÃÂ  about 85%. Construction SafetyÃÂ  ImplementationÃÂ  in the field depends on the attitude and the behavioral of the participant of construction services. The attitude of K3 depends on many factors, among others - which will be studied through this research - are: education, experience, certification, and corporate commitment. FromÃÂ  these variousÃÂ  factors, educationalÃÂ  factorsÃÂ  correlatedÃÂ  0.30ÃÂ  (significance:ÃÂ  0.048)ÃÂ  contributeÃÂ  toÃÂ  attitudeÃÂ  ofÃÂ  K3ÃÂ  ,ÃÂ  andÃÂ  was anotherÃÂ  factorÃÂ  correlationsÃÂ  wereÃÂ  notÃÂ  significant.ÃÂ  AllÃÂ  theseÃÂ  factorsÃÂ  have ÃÂ onlyÃÂ  toÃÂ  giveÃÂ  efectif contribution aboutÃÂ  to 0.213ÃÂ  (21.3%) ofÃÂ  the attitudeÃÂ  factor K3.ÃÂ  It meansÃÂ  that about ofÃÂ ÃÂ  78.7% hich can not be explained and is a problem to be studied again. Key words: attitude of K3, construction, participant of construction services ÃÂ  Abstrak:ÃÂ ÃÂ ÃÂ  PelaksanaanÃÂ  KeselamatanÃÂ  danÃÂ  KesehatanÃÂ  KerjaÃÂ  (K3)ÃÂ  terutamaÃÂ  diÃÂ  sektorÃÂ  konstruksi masih memprihatinkan.ÃÂ  K3ÃÂ  diÃÂ  Indonesia masih mendudukiÃÂ  urutanÃÂ  terbawahÃÂ  diÃÂ  Asean.ÃÂ  Berbagai upayaÃÂ  telahÃÂ  dilakukanÃÂ  olehÃÂ  pemerintahÃÂ  untukÃÂ  menekanÃÂ  kecelakaanÃÂ  kerjaÃÂ  menjadiÃÂ  seÃÂ  minimal mungkin. KecelakaanÃÂ  yangÃÂ  seringÃÂ  terjadi banyak diakibatkan olehÃÂ  faktor manusiaÃÂ  (humanÃÂ  factor) yaituÃÂ  sebesarÃÂ  85%.ÃÂ  PelaksanaanÃÂ  K3ÃÂ  KonstruksiÃÂ  diÃÂ  lapanganÃÂ  sangatÃÂ  tergantungÃÂ  dariÃÂ  sikapÃÂ  dan perilakuÃÂ  para pelakuÃÂ  jasaÃÂ  konstruksi. Sikap K3ÃÂ  sangatÃÂ  tergantungÃÂ  dariÃÂ  banyakÃÂ  faktor, antaraÃÂ  lain yangÃÂ  akanÃÂ  diungkapÃÂ  melaluiÃÂ  penelitianÃÂ  iniÃÂ  adalah:ÃÂ  pendidikan,ÃÂ  pengalaman,ÃÂ  sertifikasi,ÃÂ  dan komitmenÃÂ  perusahaan. DariÃÂ  berbagaiÃÂ  faktorÃÂ  tersebut,ÃÂ  faktorÃÂ  pendidikan mempunyaiÃÂ  korelasiÃÂ  ,30 (signifikansi: 0,048)ÃÂ  terhadap sikap K3, sedangÃÂ  faktorÃÂ  lainnya korelasinyaÃÂ  tidak signifikan. Semua faktorÃÂ  tersebut hanya memberi memiliki sumbangan efektif sebesar 0,213 (21,3%)ÃÂ  terhadapÃÂ  faktor sikapÃÂ  K3.ÃÂ ÃÂ ÃÂ  HalÃÂ  ituÃÂ  menunjukkanÃÂ  bahwaÃÂ  masihÃÂ  adaÃÂ ÃÂ ÃÂ  78,7ÃÂ  %ÃÂ  yangÃÂ  belumÃÂ  dapatÃÂ  dijelaskanÃÂ  dan merupakan masalah yang masih harus diupayakan jawabnya. Kata kunci: sikap K3, konstruksi, pelaku jasa konstruksi